2010
DOI: 10.1021/pr901098p
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Extracellular Matrix Proteins of Rice (Oryza sativa L.) Involved in Dehydration-Responsive Network: A Proteomic Approach

Abstract: Water-deficit or dehydration impairs almost all physiological processes and greatly influences the geographical distribution of many crop species. It has been postulated that higher plants rely mostly on induction mechanisms to maintain cellular integrity during stress conditions. Plant cell wall or extracellular matrix (ECM) forms an important conduit for signal transduction between the apoplast and symplast and acts as front-line defense, thereby playing a key role in cell fate decision under various stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 82 publications
3
92
0
Order By: Relevance
“…PAL, which catalyzes the deamination of phenylalanine to trans-cinnamate, was shown to be regulated upon stress exposure. In the present study, both the bacterial isolate and salinity enhanced PAL activity, is supported by Pandey et al (2010), who reported an increased level of PAL following drought stress in rice.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…PAL, which catalyzes the deamination of phenylalanine to trans-cinnamate, was shown to be regulated upon stress exposure. In the present study, both the bacterial isolate and salinity enhanced PAL activity, is supported by Pandey et al (2010), who reported an increased level of PAL following drought stress in rice.…”
Section: Discussionsupporting
confidence: 85%
“…The PAL enzyme play positive role plant cell wall lignification and down-regulation of PAL enzyme effect the lignification process in plants (Ogras et al, 2000). Pandey et al (2010) in a proteomic study, reported an enhanced PAL activity under drought stress in rice. Terzi et al (2013) also reported that, PAL activity increased up to 16-fold and also effects the polyphenol oxidase activities, ionically wall-bound peroxidase and lignin content in grey-maranta (Ctenanthe setosa) when exposed to drought stress.…”
Section: Introductionmentioning
confidence: 98%
“…However, studies using tobacco have shown the opposite regulation of this pathway during drought-induced and heat-induced stress [64]. This evolutionary divergence in stress responses among different plant species has also been shown by previous studies [22,23].…”
Section: Effects Of Drought-induced Stress On Rice Leavessupporting
confidence: 68%
“…Choudhary et al [22] analyzed drought responsive nuclear proteins in rice and revealed coordinated responses between both regulatory and functional proteins. Pandey et al [23] reported differentially regulated proteins in the extracellular matrix that are involved in carbohydrate metabolism, cell defense and rescue, cell wall modification, cell signaling, and molecular chaperones. Integrated analysis of transcriptomics, proteomics and metabolomics, which is key to the study of rice proteomics [24], provides a more effective study of regulatory mechanisms in plants.…”
Section: Introductionmentioning
confidence: 99%
“…For analysis of dehydration stress, proteomes of the extracellular matrix (ECM) and nucleus have been analyzed in rice (Pandey et al 2010) and chickpea .…”
Section: Summary Of the Research Work Carried Out In India And Nepalmentioning
confidence: 99%